1993
DOI: 10.1677/joe.0.1390441
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and galactopoietic response to recombinant variants of bovine growth hormone

Abstract: Two studies were designed to examine the pharmacokinetic and galactopoietic potency of three molecular variants of recombinant-derived bovine GH (rbGH): [Met1, Leu127]-bGH, [Ala1, Val127]-bGH and [Ala1, Val127, His133]-bGH. Histidine substitution for arginine at residue 133 of rbGH was shown to impart thrombin resistance. In a Latin square design, nine lactating Holstein cows received a 25 mg rbGH bolus infusion via the jugular vein followed by frequent blood sampling over the next 12 h. The serum GH concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…The values in the present study regarding the Leu The effects found were in line with those from the recombinant bGH efficacy study of Eppard et al [6]. Moreover, an association of the Val allele with milk production ability was suggested by Sabour …”
Section: Discussionsupporting
confidence: 92%
“…The values in the present study regarding the Leu The effects found were in line with those from the recombinant bGH efficacy study of Eppard et al [6]. Moreover, an association of the Val allele with milk production ability was suggested by Sabour …”
Section: Discussionsupporting
confidence: 92%